The application of NFT in art education: the impact on teaching, the market and certification - Hao, Yang; Dr. KHAIRUL ZAHAR BIN JAMALUDIN (International Theory and Practice in Humanities and Social Sciences, 2025)
NTF (non-fungible token), as a significant application of blockchain technology, is reshaping the model of art education. This paper explores the potential applications of the NTF in art education, focusing on how it influences teaching methods, the value transformation of students, the evaluation of art education, and international development. The study employs a mixed-method approach, combining questionnaire surveys (N=100) and semistructured interviews (N=15), to analyse the acceptance and impact of the NTF in art education. The results show that the NTF can increase students’ market awareness and copyright protection awareness and promote the global circulation of artworks. However, technical barriers, market volatility, and insufficient educational practice experience remain the main challenges to the widespread application of the NTF in art education. This research not only reveals the value of the NTF in art education but also provides practical guidance for future curriculum design, educational assessment, and academic certification.